Análise de dados e proposta de apresentação de padrões circulares para a elaboração de um guia fenológico de plantas do cerrado - Fernandes, Isnai [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The Cerrado vegetation occurs in great part of the Brazilian territory, being the second largest biome of this country. The Cerrado presents areas with high biodiversity and spans three of the largest Brazilian watersheds. However, it has been suffering serious damages caused by human activities; it is considered a global biodiversity hotspot; such as the replacement of its native vegetation for habitational areas, monoculture plantations and pasture. Phenology is the study of the occurrence of repeted events over time in plants and animals, and possible relations between these events and biotic and/or abiotic factors. In the case of plants it studies the reproductive, i.e. flowering and fruiting, and vegetative patterns, flushing and leaf fall, and the relationship of these events with factors, such as, climate and plant-animals interactions. Phenological studies are important, for example, to understand the structure of a vegetation, plant reproduction and the temporal offer of resources in communities, contributing to understand the ecology of species and communities. The objective of this study was to analyze and study the vegetative (leaf fall and flush) and reproductive (bud flower, anthesis, unripe and ripe fruits) phenological patterns of 103 cerrado's woody species, which will compose a phenological guide, for a cerrado area. We organized and analyzed the phenological data collected among six years to determine the following phenological parameters: the onset, peak and duration of the phenophases, phenological strategies (annual, subannual or continuous) and phenophases peak season (dry or wet). Using these data we elaborated circular diagrams, separately for the vegetative (leaf fall and flush) and reproductive (anthesis and ripe fruit) phenophases that will be used to represent the phenological patterns of each species in the guide. This guide is of great importance to this region of occurence...

A vegetação do cerrado distribui-se por grande parte do território brasileiro, sendo o segundo maior bioma do país, apresenta áreas com elevada biodiversidade e é berço de três grandes bacias hidrográficas brasileiras. Mesmo tendo expressivo destaque em biodiversidade e riquezas naturais, sendo considerado um dos hotspots mundiais de biodiversidade, o cerrado brasileiro vem sofrendo sérios danos causados pelo homem, principalmente com a substituição de sua vegetação nativa por áreas para assentamento populacional, plantações de monoculturas e estabelecimento de pastagens. A fenologia é um estudo das ocorrências de determinados eventos que se repetem através do tempo e sua relação com fatores bióticos e/ou abióticos. No caso das plantas, seria o estudo dos seus padrões reprodutivos, floração e frutificação, e vegetativos, crescimento e troca de folhas, e a relação destes eventos com fatores como o clima e interações com animais. Esses estudos são importantes, por exemplo, para a compreensão da estruturação da vegetação, reprodução das plantas e organização temporal dos recursos nas comunidades, contribuindo para o entendimento da ecologia das espécies e comunidades. Este trabalho teve como objetivo a análise e estudo dos padrões fenológicos vegetativos (brotamento e queda foliar) e reprodutivos (botão, antese, frutos imaturos e maduros) de 103 espécies de plantas do cerrado, que irão compor um guia fenológico e de identificação de espécies para uma área de cerrado. Para tanto, dados de seis anos de observações fenológicas foram organizados e analisados a fim de determinarmos os seguintes parêmetros fenológicos: início, pico e duração das fenofases, estratégia (anual, subanual ou contínua) e estação de pico das fenofases (seca ou úmida). A partir destes dados foram elaborados gráficos circulares, separadamente para as fenofases vegetativas...
Keywords: Cerrados; Plantas dos cerrados; Plantas - Manuais, guias, etc; Fenologia vegetal; Ecossistemas; Ecologia vegetal; Plantas - Identificação; Plantas - Reprodução; Brasil